Study of adsorption behavior of HCN and H2S molecules over undoped and Al-doped zinc oxide monolayer: A DFT approach - Dipak Oli; Om Shree Rijal; Ravi Kiran Neupane; Pitamber Shrestha; Shriram Sharma; Leela Pradhan Joshi; Rajendra Parajuli (Results in Surfaces and Interfaces)
Gas adsorption sensors are of immense importance for detecting and measuring of the presence of toxic gases to prevent health hazards, industrial accidents etc. This work investigates adsorption mechanisms of HCN and H2S on undoped and Al-doped ZnO (Al–ZnO) monolayers by examining the structural, electronic, and magnetic properties. We utilized spin-polarized Density Functional Theory with GGA-PBE, meta GGA-SCAN, and DFT + U functionals for all calculations. The adsorbed and unadsorbed ZnO monolayers exhibited non-magnetic behavior, whereas doped monolayers exhibited magnetic behavior in both adsorbed and unadsorbed states. The adsorption energies for HCN and H2S in undoped ZnO are −2.08 & −2.88 eV respectively, whereas the adsorption energies for HCN and H2S in Al–ZnO are −4.27 & −4.63 eV respectively. These results indicate that the sensitivity is enhanced with doping. Hence, Al–ZnO exhibits favorable characteristics in the adsorption of HCN and H2S gases, making it suitable for sensing toxic gases.